Bases de schiff derivadas de chalcona e de nitrogênio mostarda e seus complexos metálicos : atividade citotóxica em células tumorais e interação com biomoléculas - Luciana Batista de Paulo Sâmia (2018)
The present study consisted of the investigation of Schiff bases containing chalcona and mustard nitrogen pharmacophoric groups, as well as their platinum (II), palladium (II) and gold (III) complexes for the development of new antitumor drug candidates. The complexes [Au(L1)Cl]Cl (1), [Pt(L1)Cl]0.5KCl (2), [Pd(L1)Cl]KCl (3) and[Cu(L1)Cl] (4) with 3-(4-bromophenyl)-1-pyridin-2-ylprop-2-en-1-onethiosemicarbazone(HL1) were obtained. The cytotoxic activity of the compounds against leukemic and solid tumor cell lines and against non-tumor cells Vero was evaluated. In general, 4 was more active against the tumor cell lines tested, with better results against the JURKAT and THP-1 leukemiclines and MCF-7 breast cancer cells, being 6 to 13 times more active than the free ligand. However, the complex was also the most toxic in VERO healthy cells. Complex (1) was more active than the free ligand against most of the tumor cell lines tested. When compared to 4, 1arouses interest due to its selectivity, since it did not present toxicity in the VERO healthy cells. Complexes (2) and (3) were inactive. The mode of action of complexes (1) and (4) was investigated by studies in vitro of theinhibitory activity of the enzymes Thioredoxin Redutase (TrxR) and Topoisomerase IB (Topo IB) and by interaction studies of the compounds with plasmid DNA. The ligand (HL1) and CuCl2 did not inhibit the enzyme TrxR. The IC50 values obtained for the inhibition of TrxR enzyme activity were: complex (1) IC50 = 5.55 M; auranofin IC50 =0.30 M; HAuCl4 IC50 = 0.62 M; complex (4) IC50 = 9.63 M. Thus, TrxR could be a target for the cytotoxic action of complexes (1) and (4).Complexes (1) and (4) dose-dependently inhibited Topo IB activity. After preincubation of the enzyme with the compounds prior to DNA addition, an improvement in the inhibitory effect of the compounds was observed. At a concentration of 1.5 M, 1 completely inhibited the enzyme. It is important to note that HAuCl4 alone was able to inhibit the Topo IB,but in this case, the inhibition is never complete. For 4 the complete inhibition of the enzymatic activity is verified for the concentration of 0.75M. No inhibitory effect was observed after incubation of the enzyme with the free thiosemicarbazone or with CuCl2 up to the concentrationof 50 M. In the presence of 12 M of 4 the cleavage step was strongly inhibited and partial inhibition was observed at the religation step. Experiments of molecular docking showed that the coordination to the metal ligand adopts a proper conformation for interaction in the activesite of Topo IB. Studies of the interaction of the compounds with the DNA revealed that the complexes (1) and (4) do not interact directly with the DNA. In the second part of the present work, three hydrazones containing the mustard nitrogen group were obtained: 4-[bis(2-chloroethyl)amino]benzaldehyde]phenylhydrazone (HL2), 4-[bis(2-chloroethyl)amino]benzaldehyde]-para-chlorophenylhydrazone (HL3) and 4-[bis(2- chloroethyl)amino]benzaldehyde]-methylhydrazone (HL4). Due to the low affinity of gold (III) for ligands containing oxygen as donor atoms, it was not possible to obtain gold complexes ofthe hydrazones studied here. Three thiosemicarbazones were also obtained: 4-[bis(2- chloroethyl)amino]benzaldehyde-N(4)-phenylthiosemicarbazone (HL5), 4-[bis(2-chloroethyl)amino]benzaldehyde-N(4)-para-chlorophenylthiosemicarbazone (HL6) and 4- [bis(2-chloroethyl)amino]benzaldehyde-N(4)-methylthiosemicarbazone (HL7) and the complexes [Au(L5)Cl2]2HCl (5), [Au(L6)Cl2]2HCl.2H2O (6) and [Au(L7)Cl2]2HCl.H2O (7). The cytotoxic activity of the compounds was evaluated against melanoma cell lines, lung cancer, breast cancer and healthy cells. In general, the compounds were not active againstthe tested cell lines. However, HL5 showed selective and specific activity against B16F10 melanoma cells. Due to the specificity of HL5, studies of this compound were amplified for different melanoma cell lines. In this step, the structural analogue HL2 was also tested and found to be inactive. Gold complexes also appear to be poorly active as cytotoxic agents. A study of the mechanism of action of HL5 has shown that its antimelanoma effects occur through the induction of cell death by necrosis in B16F10 cells. HL5 probably increases the sensitivity of cells to chemotherapeutic agents and could be used in combination withantimelanoma drugs. To attempt to explain why only HL5 was able to induce cytotoxic effects, theoretical studies were conducted, which indicated that all binders and gold complexes would have thesame ability to act as DNA alkylating agents, suggesting that either the alkylation does not occur or, if it occurs, would not be a determining process for the mechanism of action of HL5. As the HL2, HL5-HL7 ligands show very distinct values of logP, the hypothesis thatonly HL5 has the proper characteristics of lipophilicity to interact with the biological target can not be ruled out. Studies of interaction of the compounds with DNA revealed that the antiproliferative effect of HL5 and 5 observed in tumor cells does not occur through the direct interaction of this compound with DNA.